Children on their birthdays [videorecording (DVD)] - Lee, Sheryl; McDonald, Christopher, 1955-; Pichler, Joe, 1987-; Raymonde, Tania, 1988-; Plemons, Jesse, 1988-; Frelich, Phyllis; Arnold, Tom, 1959-; Shaw, Steve, 1965-; Levin, Sidney; Vannelli, Ross; Hinton, J. D.; Hurley, Jay; et al. (2003)
Billy Bob is a thirteen-year-old boy growing up in a small Alabama town in 1947. Billy Bob's best friend is Preacher Star, who has a pronounced mischievous streak. When Lily Jane moves into town with her mother, a strange woman who never speaks, both Billy Bob and Preacher are entranced. Billy Bob and Preacher become rivals for Lily Jane's affections. As Billy Bob struggles with first love, he also has to deal with his mother's budding romance with Speedy, the local auto mechanic.